Ultrasound Generation: Polydimethylsiloxane Composites for Optical Ultrasound Generation and Multimodality Imaging (Adv. Funct. Mater. 9/2018). (26th February 2018) - Noimark, Sacha; Colchester, Richard J.; Poduval, Radhika K.; Maneas, Efthymios; Alles, Erwin J.; Zhao, Tianrui; Zhang, Edward Z.; Ashworth, Michael; Tsolaki, Elena; Chester, Adrian H.; Latif, Najma; Bertazzo, Sergio; et al.
Abstract : In article number1704919, Adrien E. Desjardins and co‐workers review poly(dimethylsiloxane) (PDMS) composites for optical ultrasound generation via the photoacoustic effect. Fabrication methods are classified, and recent advances that allow for deposition with micron‐scale precision on irregular substrates are highlighted. Using new methods, the authors create composites, which enable high‐resolution all‐optical ultrasound and photoacoustic imaging of biological tissue with structural and molecular contrast.